2020
DOI: 10.1177/0734016820971033
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Sex Offender Registration and Notification: Does Awareness Differ Across Community Type?

Abstract: In recent decades, sex offender registry and notification has become ubiquitous across the United States. Although researchers have attempted to evaluate the awareness of registered sex offenders, much of this work has had a nearly unilateral focus on urban communities. In response, researchers have called for further investigation into whether awareness manifests differently across community type (suburban and urban). To address this question, we draw from two data sets. The first data set contains property d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Prior content analyses have shown that registry information is heterogeneous across states, emphasizing the importance of understanding user experiences with publicly shared information as it can affect its circulation (Brewster et al, 2012; Harris et al, 2020; Mustaine & Tewksbury, 2013; Navarro et al, 2022; Tewksbury & Higgins, 2005). Online registries were in their nascency when Tewksbury and Higgins (2005) conducted their content analysis, identifying 28 registry elements across 40 state registries that were publicly accessible online at that time.…”
Section: Usage and Content Of Sex Offender Registriesmentioning
confidence: 99%
“…Prior content analyses have shown that registry information is heterogeneous across states, emphasizing the importance of understanding user experiences with publicly shared information as it can affect its circulation (Brewster et al, 2012; Harris et al, 2020; Mustaine & Tewksbury, 2013; Navarro et al, 2022; Tewksbury & Higgins, 2005). Online registries were in their nascency when Tewksbury and Higgins (2005) conducted their content analysis, identifying 28 registry elements across 40 state registries that were publicly accessible online at that time.…”
Section: Usage and Content Of Sex Offender Registriesmentioning
confidence: 99%